Four-week repeated dose oral toxicity study of KDS2010, a novel selective monoamine oxidase B inhibitor, in Sprague Dawley rats - Kim, Kyung-Tai; Kim, Da-Hee; Kim, Bo-Kyung; Han, Ji-Seok; Eom, Han Young; Yang, Mi-Jin; Shin, Seung-Hyuk; Cho, Doo-Wan; Jang, Bo Ko; Park, Ki Duk; Yang, Young-Su; Han, Su-Cheol (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
Repeated dose oral toxicity and toxicokinetic of KDS2010, a new drug for Parkinson's disease, was investigated after 4-week repeated oral administration at 30, 50, 75, or 100 mg/kg/day in rats. Body weight and body weight gain decreased in rats of both sexes in the 75 and 100 mg/kg groups, and food consumption was reduced in male rats of the 75 and 100 mg/kg male groups. Histological alterations were observed in the kidney (urothelial hyperplasia, inflammatory cell infiltration in the renal pelvis, tubular vacuolation/degeneration, basophilic tubules, and hyaline droplets in the proximal tubules) of the 75 and 100 mg/kg male groups and the 50 and 100 mg/kg female groups. The 75 and 100 mg/kg male groups showed adverse effect in the testes (degeneration/exfoliation of germ cells, seminiferous tubules atrophy) and epididymis (cellular debris, oligospermia). These changes were partially recovered after a 2-week recovery period. However, basophilic tubules and hyaline droplets in the proximal tubules in the kidney and germ cell degeneration/exfoliation in the testis were not recovered. In toxicokinetics study, systemic exposure to KDS2010 increased proportionally in both sexes by in a dose -dependent manner. In addition, repeated administration for 4 weeks led to increased tendency of systemic exposure in both sexes compared with that in Day 1. In conclusion, KDS2010 was shown to target the kidney and testis with a no-observed-adverse-effect level of 50 and 30 mg/kg/day for males and females, respectively.
Keywords: DISEASE; SAFINAMIDE; EFFICACY